PENGARUH INVESTMENT OPPORTUNITY SET, PROFITABILITAS, DAN LIKUIDITAS TERHADAP STRUKTUR MODAL (Studi pada Perusahaan Properti dan Real Estate yang Terdaftar di Bursa Efek Indonesia Tahun 2010-2014) - Yulia, Aida; Ifaksara, Mulyanti (Jurnal Akuntansi (Media Riset Akuntansi & Keuangan), 2016)
The purpose of this research is to examine the effect ofinvestment opportunity set, profitability, and liquidityon capital structureofproperty and real estate companies listed in Indonesia Stock Exchange in 2010-2014. The research type used in this research is hypothesis testing, by using purposive sampling method and there are 120 samples of data that become the object to be researched. The data type used is secondary data obtained from the financial statements, published by the capital market reference center at the Indonesia Stock Exchange. The analysis used is multiple linear regression to test the hypothesis. The results of this research show that simultaneous of investment opportunity set, profitability and liquidityhave effect oncapital structure. Partially the research show that (1) investment opportunity set have positive effect on capital structure, (2) profitability have negative effect on capital structure,(3) liquidity have negative effect on capital structure.